Age at menarche in the Korean female: secular trends and relationship to adulthood body mass index - Ju Hyun Ahn; Se Won Lim; Bong Sub Song; Juhee Seo; Jun Ah Lee; Dong Ho Kim; Jung Sub Lim (Korean Society of Pediatric Endocrinology, 2013)
PurposeThe objective of this study is to estimate the trend in age at menarche in the Korean female and evaluate the relationship between age at menarche and adult body mass index (BMI), which is a indicator of later-life health.MethodsWe conducted a cross-sectional analysis of a nationally representative sample (self-reported age at menarche and measured height and weight) of 11,065 females aged 15 and older. Data were obtained from the Fourth Korea National Health and Nutrition Examination Survey (KNHANES IV, 2007-2009).ResultsWe found a statistically significant decline in age at menarche in successive birth groups, indicating a 0.726 year decrease per decade. The age at menarche in 1990-1994 year birth group was 12.60 years, which showed a significant decreased from 3.11 years in the 1980-1984 birth group. We also found a significant negative association between age at menarche and current BMI. A one-year decrease in age at menarche was associated with mean BMI increase of 0.109 kg/m2 (95% confidence interval [CI], 0.069 to 0.150) after adjustment for age. In multivariate logistic regression, the odds ratios of obesity in females with early menarche (<12 years) was 1.845 fold (95% CI, 1.441 to 2.361).ConclusionWe found that age at menarche is still falling in the Korean female. We also found that early menarche is a risk factor for obesity in adults.